Analisis Faktor-Faktor yang Memengaruhi Penggunaan IUD Pasca Plasenta - Trisna Anesa Rahmawati; Sastrawansastrawan; KarjonoKarjono (Oksitosin : Jurnal Ilmiah Kebidanan, 2024)
High maternal mortality rate and infant mortality rate in Indonesia can be suppressed by increased coverage of MKJP methods. The aim of the research was to analyze the factors that influence the use of post-placental contraceptives with IUD methods in Praya RSUD. Research design used analytical observation with case control study. The results of the research obtained the level of knowledge of the WUS and the promotion or KIE activities given by the health personnel are significantly related to the use of post-placental IUDs in RSUD Praya with a P-value of 0,000. However, the health care competence factor is not related to the use of post-placental IUDs in Praya RSUD with a P-value of 0.715. Conclusion The level of knowledge and promotional activities/KIE by health care personnel has been linked to the use of post placental IUD in RSUD Praya. Whereas health care competence has nothing to do with it.